Measuring Demisability of Bulk Metallic Glasses for Potential Satellite Applications through Ablation Experiments. Issue 12 (30th July 2020) - Bordeenithikasem, Punnathat; Roberts, Scott N.; Hofmann, Douglas C.; Ratliff, John Martin; Greene, Benton R.; Bacon, John B.; Sohn, Sungwoo; Schroers, Jan
Abstract : Bulk metallic glasses (BMGs) exhibit attractive properties for spacecraft applications. When low Earth‐orbiting satellites reenter the atmosphere at end of mission, a measure to mitigate the generation of space debris, operators must limit the number of satellite components that reach the ground to ensure public safety. Inductively coupled plasma using an argon/air mixture to simulate reentry conditions is used to study ablation of BMG and conventional spacecraft alloys. Differential scanning calorimetry is used to determine the thermal properties of the alloys. BMGs are shown to ablate similarly to aluminum alloys (Al7075) and dramatically faster than titanium alloys (Ti‐6Al‐4V). Abstract : Ablation properties of bulk metallic glasses (BMGs) compared with aluminum (Al7075) and titanium (Ti‐6Al‐4V) alloys are measured using inductively coupled plasma to simulate satellite atmospheric reentry. Supplemented by differential scanning calorimetry experiments, BMGs demonstrate comparable ablation performance to Al7075 and demise exceedingly more effectively than Ti‐6Al‐4V.